Searching for a Cultural Home: Asian American Youth in the EDM Festival Scene - Judy Soojin Park (Dancecult: Journal of Electronic Dance Music Culture, 2015)
This article investigates the recent proliferation of Asian American participants in Electronic Dance Music (EDM) festivals with a particular focus on those organized by Insomniac Events in Southern California. As Insomniac’s events aim to propagate an ethos of PLUR—Peace, Love, Unity and Respect—reminiscent of historical rave culture, these events promise a space where anyone, regardless of race, class, gender or sexuality, is accepted. Using an interview-based methodology paired with participant observation, I argue that Asian American youth’s status as “perpetual foreigners” and subsequent desire for cultural belonging have motivated their participation in events promoted by Insomniac. Nevertheless, the Asian American participants I interviewed defined notions of belonging, authenticity and subcultural capital in the EDM festival scene in relation to suburban middle-class whiteness and in opposition to urban hip-hop blackness. My research provides a much-needed study of nonwhite participants and how they negotiate their subjectivities in relation to the contemporary EDM festival scene.